2015
DOI: 10.1590/1678-457x.6688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed maturation stages on physical properties and antioxidant activity in flaxseed ( Linum usitatissimum L.)

Abstract: The changes in flaxseed constituents at different stages of maturity are reported. The physical properties and antioxidant activity of flaxseed oil during flaxseed development have been evaluated. Continuous decrease in total polyphenol content during flaxseed development. All the results showed no significant differences between HPLC-MS and TLC for quantitative determination of phospholipids classes. The fatty acid compositions of individual phospholipids were also reported. The antioxidant activity of oilsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The reduced presence of lipid oxidation products in salamis can be attributed to the antioxidative activity of the added product (Barthet et al, 2014;Herchi et al, 2015), as well as the inclusion of spices (Aguirrezábal et al, 2000) and molds (Bruna et al, 2001). In salamis produced with the complete replacement of pork fat by AVP, alcohol compounds decreased by 40%, and aldehydes by 58%.…”
Section: Tablementioning
confidence: 99%
“…The reduced presence of lipid oxidation products in salamis can be attributed to the antioxidative activity of the added product (Barthet et al, 2014;Herchi et al, 2015), as well as the inclusion of spices (Aguirrezábal et al, 2000) and molds (Bruna et al, 2001). In salamis produced with the complete replacement of pork fat by AVP, alcohol compounds decreased by 40%, and aldehydes by 58%.…”
Section: Tablementioning
confidence: 99%
“…SDG has been determined, in free form, at the early developmental stages, but, at the later developmental stages, SDG has been found in the ester-linked form and the contents of hydroxycinnamic acids and herbacetin diglucoside have increased. In other study, it has been reported that the seed maturity stage affected the antioxidant potential of flaxseeds, which has been found to be higher for flaxseeds at a mature stage [ 17 ].…”
Section: Introductionmentioning
confidence: 99%